2021
DOI: 10.1007/s00520-021-06403-6
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a source of information on breast cancer in the Arab world

Abstract: BackgroundPatients are increasingly using YouTube™ as a source of information on Breast cancer, the most frequent cancer among women. Educating patients is highly important to reduce mortality rates. This study aims to evaluate, for the rst time, Breast Cancer Videos on YouTube™ in the Arab world that hosts their highest use. MethodsIn this cross-sectional study, the most viewed 60 videos were evaluated for global quality (GQS score), reliability (modi ed DISCERN score), usefulness (content-speci c score), and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(39 reference statements)
2
12
1
Order By: Relevance
“…While better quality content is expected to be more “popular” and more “impactful,” proven data says the opposite. The general trend in literature data is less viewing of high-scoring videos, similar to our results [ 16 , 17 , 19 22 , 24 , 29 , 30 , 33 , 40 ]. We did not find any study directly comparing the popularity of educational and personal videos.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While better quality content is expected to be more “popular” and more “impactful,” proven data says the opposite. The general trend in literature data is less viewing of high-scoring videos, similar to our results [ 16 , 17 , 19 22 , 24 , 29 , 30 , 33 , 40 ]. We did not find any study directly comparing the popularity of educational and personal videos.…”
Section: Discussionsupporting
confidence: 91%
“…Also, we could not find a significant difference between educational and personal videos in terms of average duration, number of views, and number of comments. However, in the available literature, it has been reported that educational videos are generally of higher quality and almost always lower quality videos are more popular [ 16 , 19 , 20 , 22 , 24 , 30 , 36 , 40 ]. The only exception we could find is Duran et al‘s study on prostate cancer videos, in which no significant relationship was found between the quality markers (JAMA and GQS scores) and likes, comments, views, and VPI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Arabic Internet for cancer-related information can be problematic because much of it is unaccredited or unvalidated by specialists [ 7 , 8 ]. Health information is increasingly being searched for on mobile devices and social media [ 9 ] Misinformation resulting from patients’ increased uploading of cancer data to social media, blogs, and networks raises doubts about the accuracy of online information [ 10 , 11 , 12 , 13 ]. The COVID-19 pandemic has accelerated the flow of chronic illness information online, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The infodemic has resulted in a lot of true, false, and mixed information on the Internet. Non-evidence-based, untrustworthy, erroneous, deceptive, or misleading data might make information acquisition more challenging [ 7 , 12 , 13 , 14 , 15 ]. The vast amount of cancer information available online can be overwhelming, confusing, and disturbing for some patients, especially if they are unable to filter and digest it [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%